CLINICAL SPECTRUM OF WILSON’S DISEASE, A CROSS-SECTIONAL ANALYSIS FROM A TERTIARY CARE HOSPITAL IN KARACHI (The Research of Medical Science Review, 2025)
Wilson's Disease (WD) is an autosomal recessive disorder of copper metabolism with psychiatric, neurological, and hepatic manifestations. It can be diagnosed early, but most of the time, it is delayed, especially in developing countries like Pakistan where genetic testing is still unavailable. This paper fills a gap in knowledge by comparing 300 WD-diagnosed patients who presented at Abbassi Shaheed Hospital, Karachi, on the basis of the EASL 2012 criteria. The investigation sought to establish the clinical and biochemical range of WD and identify statiscal significant diagnostic markers. Data analysis employed SPSS v20. The most common presentation was hepatic (45%), then neurological (40%) and psychiatric (10%). 78% had Kayser-Fleischer rings, which was the largest group among neurologically symptomatic patients. 85% had low ceruloplasmin and 88% urinary copper excretion. Statistically significant correlations between clinical category and KF ring presence (χ² = 35.2, p < 0.001) and between clinical group and ceruloplasmin level (F = 12.45, p < 0.001) were present. These data favor the application of biochemical and ocular markers in developing countries and validate early multidisciplinary diagnostic strategies.